Effect of low doses gamma and electron irradiation on mechanical strength of Bi2Sr2CaCu2O8 (Bi-2212) superconductor ceramics - Hamid N.A.; Mohiju Z.A.; Jamal N.F.; Abdullah Y. (Trans Tech Publications Ltd, 2023)
Bismuth compounds; Calcium compounds; Ceramic materials; Copper compounds; Crystallinity; Electrons; Gamma rays; Magnesia; Microstructure; Morphology; Solid state reactions; Strength of materials; Strontium compounds; Superconducting materials; Surface morphology; Textures; Bi-2212; Defects structure; Degree of crystallinity; Electron irradiation dose; Gamma irradiation; Irradiated samples; Solid state reaction method; Weight percentages; Electron irradiation